Improving Landscape Spacious Development - Tymoshevskyi, Vladyslav; Yurko, Ilona; Shariy, Grigoriy (International Journal of Engineering and Technology, 2018)
The purpose of research resulted in recommendations development for landscapes spatial and territory organization improvement, in particular, on the basis of fields geometric parameters influence analysis. The conducted researches are focused on ordering of arable land territory, having spatial and territory unfavorable conditions for management. Analysis is carried out and estimation of fields geometrical parameters influence on mechanized cultivation is provided. The scale for assessing feasibility of crop rotation separating triangular form fields into trapezoidal form workspaces was formed. Different forms triangular plots (rectangular, equilateral, isosceles, scalene) and areas (from 6 to 72 ha) are considered during the study. For a comprehensive analysis of design decisions, economic indicators were used, namely: capital expenditures, annual expenses, additional products cost. Power polynomials were used to establish trends and describe the functional relationship between the different shapes of land plots area and the annual profit, resulted expenses and payback period. They were described by equations and graphs were constructed. Unprofitable, ineffective, expedient and optimal division of the triangular different types areas into trapezoidal form workspaces are presented in the table. The obtained results can be used in land management projects development for territories spatial development, territory organization, rational use organization and land protection.Â